Refining the biopsychosocial model for musculoskeletal practice by introducing religion and spirituality dimensions into the clinical scenario. (June 2019) - Zegarra-Parodi, Rafael; Draper-Rodi, Jerry; Cerritelli, Francesco
Abstract: Addressing religion and spirituality (R/S) dimensions may be uncomfortable for patients and practitioners because they refer to intimate beliefs about existence, vary across the globe and cultures, and are not routinely shared in the modern therapeutic scenario. Often, R/S dimensions are overlooked in musculoskeletal (MSK) practice despite associations with attitudes and behaviour that directly affect quality of life and health outcomes. Inclusion of basic R/S dimensions in the therapeutic alliance may optimise care and establish these dimensions as interactors within the biopsychosocial model. The purpose of this commentary was to provide practitioners with definitions of R/S that are useful for managing care of MSK patients, describe how attitudes towards R/S may be linked to health status, and indicate how R/S dimensions could be discussed in simple ways in a modern therapeutic scenario. Finally, suggestions are provided for MSK practitioners and researchers to address R/S dimensions in Western evidence-oriented healthcare. Highlights: Cultural competencies in healthcare include religion/spirituality dimensions. Religion/spirituality dimensions are overlooked in Western manual care. Religion/spirituality within the biopsychosocial model may be clinically relevant. Explicit inclusion of religion/spirituality may optimise the therapeutic alliance.